2004
DOI: 10.1128/iai.72.2.1155-1158.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Ferritin-Like Dps Protein Is Required for Salmonella enterica Serovar Typhimurium Oxidative Stress Resistance and Virulence

Abstract: Resistance to phagocyte-derived reactive oxygen species is essential for Salmonella enterica serovar Typhimurium pathogenesis. Salmonella can enhance its resistance to oxidants through the induction of specific genetic pathways controlled by SoxRS, OxyR, S , E , SlyA, and RecA. These regulons can be found in a wide variety of pathogenic and environmental bacteria, suggesting that evolutionarily conserved mechanisms defend against oxidative stress both endogenously generated by aerobic respiration and exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 30 publications
(27 reference statements)
7
119
0
6
Order By: Relevance
“…The peroxiredoxin domain of PGdx has a role in protection (3,4,92). Similarly, in Salmonella enterica serovar Typhimurium, Dps protects against H 2 O 2 -derived oxidative stress and is needed for bacterial survival after phagocytosis by macrophages, as shown in a mouse model of infection (27). Dps' protective function is derived from its ability to bind Fe 2ϩ and abrogate H 2 O 2 -induced hydroxy radical production via the Fenton reaction; H 2 O 2 treatment of Fe 2ϩ -DNA complexes, in the absence of Dps, leads to the total degradation of the DNA (89).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peroxiredoxin domain of PGdx has a role in protection (3,4,92). Similarly, in Salmonella enterica serovar Typhimurium, Dps protects against H 2 O 2 -derived oxidative stress and is needed for bacterial survival after phagocytosis by macrophages, as shown in a mouse model of infection (27). Dps' protective function is derived from its ability to bind Fe 2ϩ and abrogate H 2 O 2 -induced hydroxy radical production via the Fenton reaction; H 2 O 2 treatment of Fe 2ϩ -DNA complexes, in the absence of Dps, leads to the total degradation of the DNA (89).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins involved in such processes include catalase, which decomposes H 2 O 2 , and members of both the AhpCF/TsaA family of alkylhydroperoxidases and the organic hydroperoxide resistance proteins (Ohr) that decompose organic peroxides. Also, DNA-binding ferritin-like proteins (Dps) sequester free iron and bind to DNA, thus protecting DNA from damage (27,33,45,53,59,60,67). In addition, many bacterial species possess genes encoding OxyR, a global regulator of antioxidant defenses (24, 66).…”
mentioning
confidence: 99%
“…H 2 O 2 ) (17)(18)(19)(20), nutrient starvation (13,15,21), and the presence of ethanol (15,16). Although Dps proteins are not essential for cell viability under normal growth conditions, it was shown that Dps deletion mutants of some bacteria are susceptible to oxidative stress (22)(23)(24), acids, bases, or UV radiation (25). Dps proteins can be induced by increasing iron concentrations in the medium (18) and may be up-regulated during iron starvation (19,26).…”
mentioning
confidence: 99%
“…We also constructed sep22-defective Salmonella mutants and examined the correlation between expression of SEp22 and pathogenicity to BALB/c mice using these mutants together with the wild-type parental strain (12,13,Amano et al,manuscript in preparation). In the course of our study on SEp22, Halsey et al reported the involvement of Salmonella Dps in the pathogenicity of Salmonella infection in a gene-targeting study (7). However, regulation of SEp22 expression especially with respect to virulence of environmental isolates remains largely unknown.…”
Section: Introductionmentioning
confidence: 96%
“…We analyzed sequences of N-terminal 22 amino acids of SEp22, and performed cloning of the sep22 gene covering full length coding of nucleotide sequences corresponding to 168 amino acids. The sep22 gene was shown to be similar to E. coli dps/ pexB, and subsequently to be identical to Salmonella dps (7). We also constructed sep22-defective Salmonella mutants and examined the correlation between expression of SEp22 and pathogenicity to BALB/c mice using these mutants together with the wild-type parental strain (12,13,Amano et al,manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%